The comparison of indigenous cultural religiosity in Buleng and Kentrung's preamble as oral traditions - Puspitasari, Nur Aini; Damaianti, Vismaia S.; Syihabuddin; Sumiyadi (Universitas Muhammadiyah Malang, 2024)
The preamble of oral tradition embodies a collection of beliefs and rituals practiced by indigenous people. There has been a harmonious relationship between humans and nature since ancient times. This includes the preambles of Buleng from Betawi and Kentrung from Java, which trace the religious evolution from Hindu-Buddha ancestry to Islam in Java. This study aims to compare the differences in the religiosity and culture of indigenous people in the preambles of Buleng and Kentrung. The researcher combines Koetjaraningrat's theory of cultural elements and Thompson's folklore motifs with a motif, type, and theme approach in Jost's literary comparison. This research uses a qualitative descriptive method, including transcription, identification, meaning, and comparison of data findings. The researcher applied analytical techniques of data reduction, categorization, and presenting descriptive interpretations along with the results of an outline scheme and inferring data through certain expressions of identity. The results demonstrate that: [1] both preambles express Islamic religiosity through regional language; [2] the religious system is described in all linguistic terms, acknowledging the magic of mantras in the Buleng preamble and the realization of Islamic worship in the Kentrung preamble; and [3] the social system regarding “Pancakaki” or family structure, “Sampurasun” greeting in the Betawi indigenous community, krama alus as well as the “unggah-ungguh” culture in the Javanese indigenous community are highlighted. The two preambles emphasize the dominance of Islamic religiosity, which coexists alongside respect for ancestors through wise and virtuous attitudes.